Spanish-moroccan Families in a Context of Family Diversity in Spain. Challenges for the Construction of Interculturalism - Vázquez-Aguado, Octavio; Fernández-Borrero, Manuela A.; Álvarez-Pérez, Pablo; Harris, Victor William (Journal of Tourism, Sustainability and Well-being, 2015)
This paper presents an analytical approach to the reality of Spanish-Moroccan families in Spain, constructed from two areas of data collection. The first was collected from available intermarriage data (in which at least one of the two members of the couple was Moroccan) and the second from the available data about children of these unions. The analyses were performed using official data collected in the Statistical Bulletin of Birth from the National Institute of Statistics (NIS henceforth). Since 2008, the Moroccan community has constituted the second largest contingent of foreign residents in Spain (after Romanians), although its historical trajectory places them as the immigration group with higher sociodemographic relevance. The Moroccan migration is the result of young people who marry at young ages with a strong trend toward marrying homogamously within their own national group who journey to Spain and reside primarily in larger regions such as Madrid, Valencia, Andalusia and Catalonia. The results of this study indicate that couples who are both Moroccan parents show some different marriage patterns when compared to couples where only one parent is of this nationality